Characterization of cracking on granite polygonal in Pedriza de Manzanares and Cenicientos, Madrid (Central System) - García Rodríguez, M.; Gómez Heras, M.; Alvarez de Buergo, M.; Fort González, R.; Centeno Carrillo, J.D. (M+A. Revista Electrónica de Medioambiente, 2014)
The granitoid of the core or the Spanish Central Range where intruded in the late Variscan orogeny. The show a wide petrological variety and several sets of fractures, both related to late Variscan and Alpine orogenies. These fractures influence the landforms (from hundred-meter walls to boulders) in which polygonal cracking appears in different forms. This work shows the results of a first inventory and description of polygonal cracking in two areas of the Spanish Central Range: the Pedriza de Manzanares (dominated by rock walls and tors) and Cenicientos (dominated by boulders and kopjies), both in the province of Madrid.
Keywords: National Park Sierra de Guadarrama; Pedriza de Manzanares; Cenicientos; polygonal cracking; granite weathering.